Design and Build a Flutter-Based PKKMB Application with a QR Code Feature at Narotama University - Fredy Pradana Putra; Slamet Winardi (Universitas Ahmad Dahlan, 2024)
Introduction to Campus Life for New Students (PKKMB) at Narotama University is a mandatory activity for new S1 students to get to know the academic and non-academic aspects as a condition for submitting a thesis proposal exam. The success of PKKMB is measured by the completion of tasks by participants, but manual recording for attendance, task grades, and compliance violations is prone to errors and fraud. This study uses a qualitative method that includes views, opinions, experiences, and open-ended questions to obtain the perspective of the respondents. Interviews with the chairman of the committee and participants of PKKMB 2023 were conducted to determine application features through the stages of requirements, design, implementation, testing, and maintenance. After determining the features of the application, the next step is to collect data through observation, interviews, and documentation, which are then analyzed through the stages of examination, classification, and drawing conclusions. The implementation of the PKKMB application includes splash screen pages, logins, participant homepages, participant assignments, graduation announcements, participant personal data, committee homepage, committee attendance, committee duties, and committee violations. The application was tested using the System Usability Scale with 30 respondents, resulting in a final score of 82.5 for the committee and 83 for the participants, which shows that the system is easy to use. The app is designed with Flutter, QR Code features, Laravel, and interface design from Figma.